2023
DOI: 10.1186/s40164-023-00394-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting E3 ubiquitin ligases to reeducate the tumor microenvironment for cancer therapy

Abstract: Tumor development relies on a complex and aberrant tissue environment in which cancer cells receive the necessary nutrients for growth, survive through immune escape, and acquire mesenchymal properties that mediate invasion and metastasis. Stromal cells and soluble mediators in the tumor microenvironment (TME) exhibit characteristic anti-inflammatory and protumorigenic activities. Ubiquitination, which is an essential and reversible posttranscriptional modification, plays a vital role in modulating the stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 237 publications
(233 reference statements)
0
7
0
Order By: Relevance
“…PROTACs have been described to enhance anticancer immunotherapy by regulating specific proteins, including IDO1, PD-L1, SHP2, HDAC6, HPK1, BCL-xL, BET, NAMPT, and COX-1/2. While the specific role of ubiquitination signaling in the immune defense is still unclear and the immunotherapies targeting ubiquitination are not fully understood, the interplay of the ubiquitin system and TME deserves more investigations in the future [12].…”
Section: Ubiquitin Ligases In Cancer Immunotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…PROTACs have been described to enhance anticancer immunotherapy by regulating specific proteins, including IDO1, PD-L1, SHP2, HDAC6, HPK1, BCL-xL, BET, NAMPT, and COX-1/2. While the specific role of ubiquitination signaling in the immune defense is still unclear and the immunotherapies targeting ubiquitination are not fully understood, the interplay of the ubiquitin system and TME deserves more investigations in the future [12].…”
Section: Ubiquitin Ligases In Cancer Immunotherapymentioning
confidence: 99%
“…Although only a few E3 ligases have been used in PROTACs technology, they have several advantages, including good solubility and cell permeability, and are therefore promising for the future. While the specific role of ubiquitin signaling in the immune system is still unclear and the immunotherapies targeting ubiquitination are not fully understood, the interplay of the ubiquitin system and TME deserves more investigations in the future [12]. Ubiquitin signaling is involved in several aspects of the tumor microenvironment (TME), and its dysregulation may contribute to tumor progression.…”
Section: What Effect May the Ubiquitin Signaling Modulation Have On I...mentioning
confidence: 99%
See 1 more Smart Citation
“…Activated ubiquitin is then transferred to the cysteine active site of E2 and binds to it. Finally, E3 ubiquitin ligases facilitate the binding of ubiquitin to the lysine residues of the target protein, resulting in protein ubiquitination [ 150 ]. Among the E3 ubiquitin ligase families, the Cullin-Ring E3 ubiquitin ligase (CRL3) stands out as the largest in the body, forming a multi-protein complex.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of research has identified several E3 ligases as critical regulators of tumor immune responses [ 12 ]. Certain drugs targeting E3 ubiquitin ligases have demonstrated promising effects in preclinical and clinical antitumor treatments [ 13 ]. However, the specific roles of E3 ligases in cancer cells, particularly in the context of drug resistance in cancer immunotherapy, remain inadequately understood.…”
Section: Introductionmentioning
confidence: 99%